Ganarse al jefe o el arte de promocionarse - Frisch, Bob (BookaVivo, 2021)
To quickly achieve the skills of a top-level manager, Manager in 20 Minutes arrives, an unpublished edition in Spanish, based on reports from the business bible: Harvard Business Review. This collection has been designed and adapted for entrepreneurs and professionals who want to take their projects or career to the top. The reader will find what he really should know about business matters. Concise and practical, it offers the most innovative tools in direction and management. This book focuses on building your relationship with your boss and getting promoted.